Expression of human and Porphyromonas gingivalis glutaminyl cyclases in periodontitis and rheumatoid arthritis–A pilot study. (January 2019) - Bender, Philip; Egger, Andreas; Westermann, Martin; Taudte, Nadine; Sculean, Anton; Potempa, Jan; Möller, Burkhard; Buchholz, Mirko; Eick, Sigrun
Highlights: Porphyromonas gingivalis glutaminyl cyclase is expressed in vitro and in vivo. Porphyromonas gingivalis glutaminyl cyclase is located in bacterial cell wall. Human glutaminyl cyclases are expressed in periodontium of RA patients. Expression of human glutaminyl cyclases is correlated with those of interleukin-1β. Abstract: Objectives: Human glutaminyl cyclases (QC and isoQC) play an important role in maintaining inflammatory conditions. Meanwhile a glutaminyl cyclase synthesized by Porphyromonas gingivalis (PgQC), a key pathogen in developing periodontitis and a potential link of periodontitis with rheumatoid arthritis (RA), was discovered. This study was aimed to determine the expression of QC, isoQC and PgQC in patients with chronic periodontitis (CP) and RA. Design: Thirty volunteers were enrolled in a pilot study and divided into 3 groups (healthy, CP and RA individuals). Blood samples, biofilm and gingival crevicular fluid (GCF) were analysed for mRNA expression of QC, isoQC and P. gingivalis QC. Major bacteria being associated with periodontal disease were quantified in subgingival biofilm and protein levels for monocyte chemoattractant protein (MCP)-1, MCP-3 and interleukin (IL)-1β) were determined in the GCF. Expression of PgQC on the mRNA and protein levels was assessed in two P. gingivalis strains. Results: PgQC is expressed in P. gingivalis strains and the protein seems to be located mainly in peri-plasmatic space. mRNA expression of QC was significantly increased in the peripheral blood from RA patients vs. healthy subjects and CP patients (p = 0.013 and p = 0.003, respectively). In GCF of RA patients, QC mRNA was detected more frequently than in healthy controls (p = 0.043). In these samples IL-1β levels were also elevated compared to GCF from periodontally healthy individuals (p = 0.003). PgQC was detected in eight out of the 13 P. gingivalis positive biofilm samples. Conclusion: Activity of QC may play a supportive role in maintaining chronic periodontal inflammation and destruction in RA. PgQC is expressed in vivo but further research is needed to evaluate biological importance of this enzyme and if it constitutes a potential target in periodontal antimicrobial therapy.